Pengaruh Economic Value Added (EVA), Market Value Added (MVA), Likuiditas, Ukuran Perusahaan Dan Kebijakan Dividen Terhadap Harga Saham Pada Perusahaan Yang Terdaftar Di LQ-45 Pada Juli 2021- Maret 2022 - Femmy Juliastuti; Murtanto Murtanto; Hermi Hermi (Student Research Journal, 2024)
This research aims to know the effect of Economic Value Added (EVA), Market Value Added (MVA), Liquidity, Firm Size And Dividend Policy On Stock Price on companies index LQ45 in the Indonesian Stock Exchange (IDX), which were published in financial report and registered on period July 2021-March 2022. Research design was a causative research. The data population taken from companies in the Indonesian Stock Exchange (IDX) index LQ45. Sampling method used in this research is purposive sampling. There were 38 companies that fulfilled the sample criterias. So, the data sample in this research were 114. Analysis techniques consisted of regression analysis. The result of this research showed that (1) Economic Value Added does not effects on Stock Price (2) Market Value Added positivie effects on Stock Price, (3) Liquidity positivie effect on Stock Price, (4) Firm Size positivie effects on Stock Price, (5) Dividend Policy positivie effects on Stock Price.